2021
DOI: 10.2215/cjn.02690221
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19–Associated Mortality among Kidney Transplant Recipients and Candidates in the United States

Abstract: Background and Objectives: The COVID-19 pandemic has had a profound impact on transplantation activity in the United States and globally. Several single center reports suggest higher morbidity and mortality among candidates waitlisted for a kidney transplant as well as recipients of a kidney transplant. We aim to describe 2020 mortality patterns during the COVID-19 pandemic in the United States among kidney transplant candidates and recipients. Design, Setting, Participants, and Measurements: Using national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 23 publications
1
54
0
1
Order By: Relevance
“…A number of studies have confirmed that immunocompromised patients are at high risk of developing severe COVID-19 disease and of dying when infected with SARS-CoV-2 (65)(66)(67)(68). This seems to be particularly the case in patients with combined defects of B and T cell immunity as observed early after transplantation as well as in patients given intensive chemotherapy (69)(70)(71)(72)(73). Anti-CD20 therapy inducing a profound B-cell depletion also increases the risk of severe COVID-19 and death (74)(75)(76).…”
Section: Immune Response To Sars-cov-2 Mrna Vaccination In Immunocomp...mentioning
confidence: 93%
“…A number of studies have confirmed that immunocompromised patients are at high risk of developing severe COVID-19 disease and of dying when infected with SARS-CoV-2 (65)(66)(67)(68). This seems to be particularly the case in patients with combined defects of B and T cell immunity as observed early after transplantation as well as in patients given intensive chemotherapy (69)(70)(71)(72)(73). Anti-CD20 therapy inducing a profound B-cell depletion also increases the risk of severe COVID-19 and death (74)(75)(76).…”
Section: Immune Response To Sars-cov-2 Mrna Vaccination In Immunocomp...mentioning
confidence: 93%
“…Mohan et al recently reported that 16% of all deaths among kidney transplant recipients and 11% of all deaths on the kidney transplant waiting list in 2020 were due to SARS‐CoV‐2 infection. 1 An Italian survey reported a 32.7% mortality among liver transplant candidates during the public health emergency, increasing to 45% among those with a Model for End‐Stage Liver Disease (MELD) score >15. 2 It has been demonstrated that solid‐organ transplant recipients on immunosuppression tend to be hyporesponsive to COVID‐19 vaccines, particularly those taking antimetabolites.…”
Section: Introductionmentioning
confidence: 99%
“…SARS‐CoV‐2 infection causes substantial morbidity and mortality in solid organ transplant recipients (SOTRs). 1 , 2 , 3 , 4 Vaccination holds promise to reduce COVID‐19 severity in SOTRs, but a significant subset does not develop antibody response after two‐ and three‐dose mRNA vaccine series, 5 , 6 , 7 , 8 which likely contributes to higher rates of COVID‐19 breakthrough after vaccination. 4 Heterologous vaccination (“mixing platforms”) is one potential mode to augment aspects of immune sero‐response, 9 , 10 , 11 , 12 but data are limited in SOTRs.…”
Section: Introductionmentioning
confidence: 99%